(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Rapid development of industrialization and urbanization along Sungai Kerteh and Sungai Paka was become a problem due to metal pollution. Namely, anthropogenic activities nearby Sungai Kerteh and Sungai Paka were contributed to heavy metals pollution into those rivers. The aims for this study were to determine the selected heavy metal contamination in water samples and compared with National Water Quality Standard for Malaysia (NWQS). A total of 8 water samples were collected from both rivers and heavy metal concentration were analyzed using flame Atomic Absorption Spectroscopy (ASS). Four parameters of physical chemical properties were also analyzed which are pH, temperature, dissolved oxygen and turbidity. The ranges of physical chemical properties are pH (7.84-8.78), temperature (31.20 -38.70 oC), dissolved oxygen (27.90-107.20%) and turbidity (1.83-10.5 NTU) respectively. The mean of heavy metals concentration was ranged as followed; As (2323.00 ug/L) > Hg (571.93 ug/L) > Pb (402.13 ug/L) > Zn (87.13 ug/L) >Cr (74.63 ug/L) > Cu (48.50 ug/L) > Ni (17.25 ug/L) > Cd (11.38 ug/L). When compared with NWQS, most of metals (Cu, Pb, Ni and Zn) are below the NWQS threshold limit except As, Cd, Cr and Hg. The output data from this study can be used as database for continuous monitoring at both rivers.